Radish, Chinese—Raphanus sativus L. - James M. Stephens (EDIS, 2003)
This document describes the Chinese radish (Raphanus sativus L.), also known as daikon or Oriental radish, highlighting its origin, physical characteristics, and cultivation practices. It details the plant’s large root size, leaf structure, and common varieties such as ‘Chinese Rose’ and ‘Chinese White.’ The document outlines optimal growing conditions in Florida, including planting time, spacing, and soil preparation. It also discusses the radish’s culinary uses, noting its preference for cooking over raw consumption and its popularity in Asian cuisine. Original publication date May 1994.